Urban Regeneration, Rent Regulation and the Private Rental Sector in Portugal: A Case Study on Inner-City Lisbon’s Social Sustainability - Alves, Sónia (2023)
Rent regulation has a significant impact on tenant–landlord relations and the overall functioning of the private rented sector. Different forms of rent regulation—in relation to rent levels, rent increases, security of tenure, etc.—also affect the quality, the social composition and, ultimately, the size of the private rented sector. Together they affect the character of much urban regeneration and renewal. The introduction in Portugal of more flexible rent regimes that aimed to gradually replace open-ended tenancies with freely negotiated contracts led researchers to classify the country as a free market system. In this paper, by using a mixed methods approach that combined desk-based research with census data and in-depth interviews, we test the) classification of Portugal’s rented sector as a free market against empirical evidence and examine the impacts of the main rent regulation regimes on social sustainability-oriented urban regeneration. Our results show that open-ended contracts, which were signed before the 1990s, still account for a significant part of the private rented sector, thus the classification of Portugal’s rent regulation regime as a free-market system does not capture the country’s most significant features. This is particularly evident in inner-city Lisbon, where various extreme rent regimes (in terms of contract duration, tenant security and prices) coexist, giving rise to tensions between housing quality and demographic shifts that threaten the overall social sustainability of the city.